“A Few Bars of the Hymn of Hate”: The Reception of Ernst Lissauer’s “Haßgesang gegen England” in German and English - Richard Millington; Roger Smith (Studies in 20th & 21st Century Literature, 2017)
“The poem fell like a shell into a munitions depot”: with these words Stefan Zweig recalled the impact made by Ernst Lissauer’s Anglophobic poem “Haßgesang gegen England” (A Chant of Hate Against England) upon first publication in August 1914. The poem’s success derived from the rhetorical power with which it encapsulated a national emotional response to the outbreak of war. In Germany it initiated an outpouring of Anglophobic verse, but lost favor as it became clear that the patriotism it epitomized would not carry the Central Powers to a swift victory. Even after its disappearance from public attention in Germany, the international notoriety it had already achieved guaranteed it a prominence in the English-speaking world that lasted into the early interwar period. Ultimately, its role in anti-German propaganda was as great as its contribution to its original Anglophobic purpose, and the poem became a globally recognizable symbol of the German national outlook and temperament. This study draws on recently digitized newspaper and journal archives, as well as pamphlets, government records, soldiers’ diaries, and scholarly sources, to trace the reception of Lissauer’s “Haßgesang” in German and English.
Keywords: German Poetry; First World War; Ernst Lissauer; reception